Promoter-level transcriptome in primary lesions of endometrial cancer identified biomarkers associated with lymph node metastasis - Yoshida, Emiko (Sci Rep, 2017)
For endometrial cancer patients, lymphadenectomy is recommended to exclude rarely metastasized cancer cells. This procedure is performed even in patients with low risk of recurrence despite the risk of complications such as lymphedema. A method to accurately identify cases with no lymph node metastases (LN−) before lymphadenectomy is therefore highly required. We approached this clinical problem by examining primary lesions of endometrial cancers with CAGE (Cap Analysis Gene Expression), which quantifies promoter-level expression across the genome. Fourteen profiles delineated distinct transcriptional networks between LN + and LN− cases, within those classified as having the low or intermediate risk of recurrence. Subsequent quantitative reverse transcription polymerase chain reaction (qRT-PCR) analyses of 115 primary tumors showed SEMA3D mRNA and TACC2 isoforms expressed through a novel promoter as promising biomarkers with high accuracy (area under the receiver operating characteristic curve, 0.929) when used in combination. Our high-resolution transcriptome provided evidence of distinct molecular profiles underlying LN + /LN− status in endometrial cancers, raising the possibility of preoperative diagnosis to reduce unnecessary operations in patients with minimum recurrence risk.